Single Parenting and Family Conflicts in Nigeria - Onyebuchi , Amadi-Ali, Beatrice (International Journal of Formal Education, 2024)
This paper focuses on how single parenting could lead to family conflicts in Nigeria. It discusses conflict, family, family conflict, single parenting, causes of single parenting, effects of single parenting, the rate of single in some oversea countries, single parenting and family conflicts in Nigeria and steps that could be taken to prevent single parenting and family conflicts in Nigeria. The paper proffers steps that could be put in place to prevent single parenting and family conflicts in Nigeria such as husbands and wives would be ready to make sacrifices, be committed to each other, respect each other and obey hierarchy, be reasonable to each other, forgive and respect each other. The paper concludes that family conflicts would obviously arise, but when it does, should be handled wisely. Based on the conclusion, it was suggested among others that mutual understanding and respect be applied in all matters for peace to reign.